Decision-making impairments in epilepsy: behavioral and EEG evidence of event-related potential - An, Sijie; Chen, Qing; Zhou, Yuwei; Gao, Xiangyu; Gong, Siyu; An, Minghao; Liu, Yimin; Xie, Chengjuan; Jiang, Yubao; Wang, Kai; Chen, Xingui (Frontiers in Neuroscience, 2025)
ObjectiveDecision-making is impaired in patients with epilepsy; however, the changes in decision-making in patients with new-onset and seizure-remission epilepsy remain unclear. The aim of this study was to examine decision-making differences in patients with new-onset and seizure-remission epilepsy, as well as the neurophysiological mechanisms.MethodsThis study included 32 patients with new-onset epilepsy, 31 with seizure-remission epilepsy with generalized tonic–clonic seizures, and 34 matched healthy individuals. Simultaneous electroencephalogram was performed using the Iowa gambling task (IGT). Behavioral performance in the IGT was assessed among the three groups, and P300 and theta oscillations were used as electrophysiological indicators to observe decision-making ability.ResultsPatients with new-onset and seizure-remission epilepsy had significantly lower net scores, lower accounts, and lesser P300 amplitudes and theta oscillation power than did healthy individuals. The percent use of negative feedback was positively correlated with the P300 amplitude.ConclusionImpaired decision-making in persons with epilepsy is associated with decreased P300 amplitude and attenuated theta oscillations. Decision-making function was impaired despite clinical seizure-remission.SignificanceThis study is the first to compare the behavioral differences in decision-making ability between patients with new-onset and seizure-remission epilepsy. The combination of electroencephalographic features reveals neural mechanisms and improves the understanding of epilepsy decision-making.